Plasticity and Deformation Mechanisms of Ultrafine-Grained Ti in Necking Region Revealed by Digital Image Correlation Technique - Yonghao Zhao; Yanglin Gu; Yazhou Guo (Nanomaterials, 2021)
The conventional engineering stress-strain curve could not accurately describe the true stress-strain and local deformability of the necking part of tensile specimens, as it calculates the strain by using the whole gauge length, assuming the tensile specimen was deformed uniformly. In this study, we employed 3D optical measuring digital image correlation (DIC) to systematically measure the full strain field and local strain during the whole tensile process, and calculate the real-time strain and actual flow stress in the necking region of ultrafine-grained (UFG) Ti. The post-necking elongation and strain hardening exponent of the UFG Ti necking part were then measured as 36% and 0.101, slightly smaller than those of the coarse grained Ti (52% and 0.167), suggesting the high plastic deformability in the necking part of the UFG Ti. Finite elemental modeling (FEM) indicates that when necking occurs, strain is concentrated in the necking region. The stress state of the necking part was transformed from uniaxial in the uniform elongation stage to a triaxial stress state. A scanning electron microscopic (SEM) study revealed the shear and ductile fracture, as well as numerous micro shear bands in the UFG Ti, which are controlled by cooperative grain boundary sliding. Our work revealed the large plastic deformability of UFG metals in the necking region under a complex stress state.